English Teacher’s Challanges in Teaching English as Foreign Language at MTS Nurul Qolbi - Erniyanti Nur Fatahhela Dewi; Mentari Pratami (CV. Eureka Murakabi Abadi, 2022)
Teaching English as Foreign Language (TEFL) becomes a crucial issue. Meanwhile, it is not an easy task, especially when it was done in places where English has very limited purposes. This research seeks to investigate the challenges of English teachers as well as the solutions taken by English teachers in private Islamic junior high school. The data is gathered through documentation, interview, and classroom observation. This study captures the perspective of an English teacher in facing the challenges of teaching English in the classroom through interviews. Various challenges arose, results showed that the challenges facing in teaching English are varied in which they related to the students and the facilities. The challenges coming from students’ side including lack of vocabulary mastery, low concentration, lack of discipline, students’ boredom, speaking problem, confidence issue, facilities issues, and time constraint. It can be concluded that this study has highlighted a wide range of issues faced in teaching English as a Foreign Language in Madrasah Tsanawiyah Nurul Qolbi.